The Methodology of Sheikh Yūsuf al-Qaraḍāwī in Renewal and Revival: Principles, Pillars, and Peculiarities - Rasak, Mohamed Arkam Mohamed; Abdullah Latreche (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to examine the methodology of Sheikh Yūsuf al-Qaraḍāwī as a reformist pioneer in the contemporary era who established a modern renewal school distinguished by uniqueness and moderation. This made him widely accepted and appreciated among people, earning support and endorsement. This methodology did not focus solely on jurisprudential and spiritual aspects, but it went beyond that to reformist political jurisprudence, contributing to the revival of the Muslim Ummah within a renewed and pioneering civilisational transformation. In this study, we examine the core questions outlined as follows: What are the features of renewal and revival in Sheikh al-Qaraḍāwī's ijtihād? Has his school achieved the desired outcomes in the path of revival? And what are the manifestations of this successful renewal that have enriched contemporary Renaissance thought? The research employed an analytical approach of deduction, induction, and an analysis of the impact within the Sheikh’s reformist ijtihād. He examined globalisation and its intellectual tensions with Western thought through his engagement with fundamental civilisational issues. He also analysed the confrontation between secularism and Islam, affirming Islam’s capacity for governance and societal leadership. While further contributing to the renewal of religious discourse. One of his most innovative contributions was his redefinition of the concept of renewal, shifting it from the notion of an individual reformer to that of a renewing community or group. This unprecedented effort stands as a distinguished achievement to his credit. The study concluded by identifying the key features of al-Qaraḍāwī's approach to renewal and revival within the contemporary thought of a Muslim Umma aspiring toward its anticipated renaissance. It also highlighted the comprehensive and encyclopaedic diversity of his reformist intellectual contributions. Moreover, his ability to integrate theoretical and practical aspects endowed him with strength and leadership